2009
DOI: 10.1089/bfm.2008.0144
|View full text |Cite
|
Sign up to set email alerts
|

The Absence ofCandida albicansin Milk Samples of Women with Clinical Symptoms of Ductal Candidiasis

Abstract: These data suggest that C. albicans is not present in milk ducts and may not be associated with this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 17 publications
0
62
1
8
Order By: Relevance
“…[35][36][37] (I) A recent investigation of women with these typical symptoms, using breastmilk cultures after cleansing the nipples, found that none of the 35 cultures from the control group of women grew Candida, whereas only one of 29 in the symptomatic group grew the organism. 38 (I) There was also no significant difference in the measurement of a by-product of Candida growth [(1,3)b-d-glucan] between groups. 38 Yet, evidence is conflicting as another recent study on milk culture found that 30% of symptomatic mothers were positive for Candida, whereas 8% of women in the asymptomatic group grew the organism.…”
Section: Candida Infectionmentioning
confidence: 90%
See 1 more Smart Citation
“…[35][36][37] (I) A recent investigation of women with these typical symptoms, using breastmilk cultures after cleansing the nipples, found that none of the 35 cultures from the control group of women grew Candida, whereas only one of 29 in the symptomatic group grew the organism. 38 (I) There was also no significant difference in the measurement of a by-product of Candida growth [(1,3)b-d-glucan] between groups. 38 Yet, evidence is conflicting as another recent study on milk culture found that 30% of symptomatic mothers were positive for Candida, whereas 8% of women in the asymptomatic group grew the organism.…”
Section: Candida Infectionmentioning
confidence: 90%
“…38 (I) There was also no significant difference in the measurement of a by-product of Candida growth [(1,3)b-d-glucan] between groups. 38 Yet, evidence is conflicting as another recent study on milk culture found that 30% of symptomatic mothers were positive for Candida, whereas 8% of women in the asymptomatic group grew the organism. 39 (I) Women with burning nipple and breast pain may also be more likely to test positive for Candida on nipple swab by polymerase chain reaction.…”
Section: Candida Infectionmentioning
confidence: 90%
“…38,39 No obstante, con medios de detección adecuados, se siguen diagnosticando cándidas en algunos casos de dolor de pecho crónico o punzante. 21,38 Los principales factores de riesgo son vaginitis por cándidas periparto, grietas del pezón, corticoterapia o antibioterapia de amplio espectro en el parto o posparto, diabetes materna y candidiasis oral o en la zona del pañal del lactante.…”
Section: Mastitis Por Cándidasunclassified
“…28,39,48 Se ha aislado esta bacteria en la leche del 20% de mujeres con dolor crónico de pecho frente al 2% en la leche de los controles y se ha constatado la mejoría clínica con antibióticos. 7 Varios autores no encontraron relación entre SCN y el dolor crónico de pecho.…”
Section: Dolor Del Pezón Y Del Pechounclassified
“…Although it is generally accepted that acute mastitis may be caused by infections, an infectious etiology for chronic pain remains controversial. [5][6][7][8][9] Historically, many women received treatment with antifungal agents for presumed yeast infections. 7 In contrast, more recent studies have focused on a potential bacterial etiology.…”
Section: Introductionmentioning
confidence: 99%